Effect of nitrogen and sulphur on mustard (Brassica juncea) in an inceptisol - SUKIRTEE,; SINGH, Y V; RANJAN, K RISHI; BHARTEEY, P K (The Indian Journal of Agricultural Sciences, 2022)
A pot experiment was conducted at Research farm of Banaras Hindu University, Varanasi Uttar Pradesh to assess the interactive effect of nitrogen (N) and sulphur (S) on productivity, nutrient content and uptake of mustard. The 12 treatments consisted combinations of four levels of N (0, 50, 100 and 150 N kg/ha) and three levels of S (0, 25 and 50 kg S/ha), were replicated thrice in a factorial randomized design. Results showed that seed and stover yield increased significantly by 78.5% and 28.9% over control along with this 18.9% and 26.5% increment was observed in seeds/ siliqua and 1000 seed weight over control, respectively with increasing nitrogen and sulphur level up to 100 kg N/ha and 25 kg S/ha. Mustard responds to application of N and S but the response is not always synergistic for productivity of mustard and depends on the amount of nutrient present in the soil and proportion in which these two nutrients are taken up by the plant.